Genetics and Genomics Approaches for Diagnosis and Research Into Hereditary Anemias - Russo, Roberta; Marra, Roberta; Rosato, Barbara Eleni; Iolascon, Achille; Andolfo, Immacolata (Frontiers in Physiology, 2020)
The hereditary anemias are a relatively heterogeneous set of disorders that can show wide clinical and genetic heterogeneity, which often hampers correct clinical diagnosis. The classical diagnostic workflow for these conditions generally used to start with analysis of the family and personal histories, followed by biochemical and morphological evaluations, and ending with genetic testing. However, the diagnostic framework has changed more recently, and genetic testing is now a suitable approach for differential diagnosis of these patients. There are several approaches to this genetic testing, the choice of which depends on phenotyping, genetic heterogeneity, and gene size. For patients who show complete phenotyping, single-gene testing remains recommended. However, genetic analysis now includes next-generation sequencing, which is generally based on custom-designed targeting panels and whole-exome sequencing. The use of next-generation sequencing also allows the identification of new causative genes, and of polygenic conditions and genetic factors that modify disease severity of hereditary anemias. In the research field, whole-genome sequencing is useful for the identification of noncoding causative mutations, which might account for the disruption of transcriptional factor occupancy sites and cis-regulatory elements. Moreover, advances in high-throughput sequencing techniques have now resulted in the identification of genome-wide profiling of the chromatin structures known as the topologically associating domains. These represent a recurrent disease mechanism that exposes genes to inappropriate regulatory elements, causing errors in gene expression. This review focuses on the challenges of diagnosis and research into hereditary anemias, with indications of both the advantages and disadvantages. Finally, we consider the future perspectives for the use of next-generation sequencing technologies in this era of precision medicine.